Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

4(x2+2x+1)(x2+3x-2)+(x-3)2=(a2+bx+c)2 find a2+b2+c2

4(x2+2x+1)(x2+3x-2)+(x-3)2=(a2+bx+c)2
find a2+b2+c2

Grade:10

2 Answers

Nirmal Singh.
askIITians Faculty 44 Points
7 years ago

201-2493_1.png
Regards,
Nirmal Singh
Askiitians Faculty
mycroft holmes
272 Points
7 years ago
4(x^2+2x+1)(x^2+3x-2)+(x-3)^2 = 4 (x+1)^2 [(x+1)^2+(x-3)]+(x-2)^2 = 4(x+1)^4 + 4 (x+1)^2 (x-3) + (x-3)^2 = [2(x+1)^2+(x-3)]^2 = [2x^2+5x-1]^2 So a=2, b=5, c=-1

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free